CO2 Activation Within a Superalkali-Doped Fullerene - Meloni, Giovanni; Giustini, Andrea; Park, Heejune (Frontiers in Chemistry, 2021)
With the aim of finding a suitable synthesizable superalkali species, using the B3LYP/6-31G* density functional level of theory we provide results for the interaction between the buckminsterfullerene C60 and the superalkali Li3F2. We show that this endofullerene is stable and provides a closed environment in which the superalkali can exist and interact with CO2. It is worthwhile to mention that the optimized Li3F2 structure inside C60 is not the most stable C2v isomer found for the “free” superalkali but the D3h geometry. The binding energy at 0 K between C60 and Li3F2 (D3h) is computed to be 119 kJ mol-1. Once CO2 is introduced in the endofullerene, it is activated, and the ("OCO" ) ̂ angle is bent to 132o. This activation does not follow the previously studied CO2 reduction by an electron transfer process from the superalkali, but it is rather an actual reaction where a F (from Li3F2) atom is bonded to the CO2. From a thermodynamic analysis, both CO2 and the encapsulated [Li3F2CO2] are destabilized in C60 with solvation energies at 0 K of 147 and < -965 kJ mol-1, respectively.